American folk music as tactical media - Svec, Henry Adam (Recursions: theories of media, materiality, and cultural techniques., 2018)
American folk music has long presented a problematic conception of authenticity, but the reality of the folk scene, and its relationship to media, is far more complicated. This book draws on the fields of media archaeology, performance studies, and sound studies to explore the various modes of communication that can be uncovered from the long American folk revival. From Alan Lomax's cybernetic visions to Bob Dylan's noisy writing machines, this book retrieves a subterranean discourse on the concept of media that might help us to reimagine the potential of the networks in which we work, play, and sing.